Smart Parking System Using ESP32 with Real-Time Web Dashboard - Shruti Kumari; Goutam Kumar (Journal of Microprocessor and Microcontroller Research, 2026)
The rapid growth of metropolitan areas has increased the number of vehicles, which causes traffic bottlenecks and increases carbon emissions. This elevates the need for systemized parking areas. This paper presents a solution to this urban problem by implementing an IoT-based smart parking system using an ESP32 microcontroller. The data is displayed on a real-time web dashboard, making it accessible at any time and from anywhere. The proposed system integrates two infrared sensors, one at the entry point and another at the exit point, for vehicle detection. The collected data is transmitted to the web dashboard via Wi-Fi. Additionally, the data is displayed on an LCD display with an I2C module, along with a traffic light module for better visual representation. The system provides a real-time web dashboard that can be accessed from anywhere using only an IP address, without requiring any third-party application. Additionally, parking status is displayed locally on an LCD module, showing the number of available and occupied slots. When all parking slots are occupied, the LCD displays a “Parking Full” message, and the automatic gate prevents further vehicle entry. Experimental testing demonstrated reliable vehicle detection and real-time parking status updates when the IR sensors were properly calibrated and positioned. The developed prototype supports four parking slots and was implemented at an approximate hardware cost of ₹1600, ensuring timely updates to users. Hence, the system is cost-effective, user-friendly, scalable, and suitable for smart city applications, with potential room for further enhancement.